Inflammation and Natural Products - Rodríguez-Luna, Azahara; González, Salvador (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Terrestrial and marine environments are inexhaustible sources of compounds and active extracts which have been employed in medicine since ancient times. The aim of this reprint is to collect new approaches around compounds and extracts isolated from natural products and their biological activity, with a focus on anti-inflammatory pathways. Thus, this reprint compiles full original papers and reviews articles published during 2023 in a Special Issue of Life, titled "Inflammation and Natural products". The publications within this reprint are focused on secondary metabolites of plants demonstrating significant antioxidants and anti-inflammatory properties, among others, and clinical relevance in various pathological conditions. It also includes reviews that focus on natural therapies for topics such as arthritis, lung diseases, neuroprotection, skin photoprotection, and the impact of gender in the use of medicinal plants in relation to vascular diseases. The reprint of this Special Issue will serve as a reference text for researchers and academics, as well as those studying natural products and their pharmacological activities.